Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021) 2021
DOI: 10.22323/1.395.0710
|View full text |Cite
|
Sign up to set email alerts
|

Status of the VERITAS Stellar Intensity Interferometry (VSII) System

Abstract: Matthews a,d on behalf of the VERITAS Collaboration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 0 publications
6
83
0
2
Order By: Relevance
“…When the literature was reviewed, it was seen that the suicide attempt is associated with a specific disease (Ikeda et al, 2001;Wang et al, 2009). It was shown in this study that the main risk factor for a suicide attempt is the presence of any chronic disease, not the specific type of disease (somatic or psychiatric).…”
Section: Discussionmentioning
confidence: 69%
“…When the literature was reviewed, it was seen that the suicide attempt is associated with a specific disease (Ikeda et al, 2001;Wang et al, 2009). It was shown in this study that the main risk factor for a suicide attempt is the presence of any chronic disease, not the specific type of disease (somatic or psychiatric).…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have suggested that Maxent has good predictive power for birds (Hu & Liu, 2014, Wauchope et al 2017. We used occurrence records only when the subspecies present was genetically confirmed, and the breeding status was known because this approach to predicting subspecies distribution has proven more accurate than traditional methods that rely solely on occurrence records (Ikeda et al 2017).…”
Section: Species Distribution Modellingmentioning
confidence: 99%
“…VSII is implemented through an instrumentation augmentation of the existing VERITAS gamma-ray observatory. 2 VSII operates for 5-10 days/month during bright moon periods when the intensity of scattered moonlight severely limits VERITAS gamma-ray observations. This paper describes the VSII instrumentation, including recent upgrades and improvements in the VSII observatory.…”
Section: The Veritas Stellar Intensity Interferometer (Vsii) 11 Overviewmentioning
confidence: 99%
“…The observing sequence has evolved to include nightly planning of observing constraints imposed by moon location and other considerations (e.g., stellar magnitude, estimated stellar diameter, source elevation, weather, etc.) 2…”
Section: Overviewmentioning
confidence: 99%